Twenty-two years follow-up of a prospective randomized trial of hepatitis B vaccines without booster dose in children: Final report - But, David Yiu-Kuen; Lai, Ching-Lung; Lim, Wei-Ling; Fung, James; Wong, Danny Ka-Ho; Yuen, Man-Fung (Vaccine, 2008)
Long-term immunogenicity and efficacy of HBV vaccination with different regimens of HBV vaccines (A: 2-dose recombinant vs. B: 3-dose recombinant vs. C: 3-dose plasma-derived vaccines) without booster dose were examined in 318 Chinese children. Geometric mean titer (GMTs) of anti-HBs of group A subjects was significantly lower than that of groups B and C subjects at years 1, 5, 10 and 15. At year 22, the proportion of subjects with anti-HBs ≥10 mIU/mL for groups A, B and C were 35.3%, 76.5% and 52.4%, respectively ( p < 0.05 between groups A and B) in 55 subjects. In the 22 years study period, none was found to be HBsAg positive, and 72 subjects had ≥1 episodes of anamnestic response. In conclusion, the 3-dose regimens have a better long-term immunogenicity. In terms of protection against HBV infection, the 2-dose and 3-dose vaccines had equal efficacies.